2015
DOI: 10.1002/etc.3088
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle–based colorimetric aptasensor for rapid detection of six organophosphorous pesticides

Abstract: Fast immunoassay-based screening methods are unavailable for most small-molecule pesticides because of a lack of immunogenicity and the difficulty in obtaining antibodies by animal immunization. Aptamers are single-stranded DNA molecules selected through an in vitro process, which can bind to any target including nonimmunogenic small molecules with high affinity and specificity. Although various aptamer-based sensing methods have been developed for antibiotics, microorganisms, heavy metal ions, and biotoxins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 48 publications
0
44
0
Order By: Relevance
“…Aggregation of AuNPs causes a shift in the absorbance peak to 630 nm and change in colour from wine red to blue. Aflatoxin M1 specific aptamers were adsorbed onto the surface of AuNPs by physiosorption between Au and N atom in DNA base 9 . It was observed that aptamer coated AuNPs were protected against salt aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Aggregation of AuNPs causes a shift in the absorbance peak to 630 nm and change in colour from wine red to blue. Aflatoxin M1 specific aptamers were adsorbed onto the surface of AuNPs by physiosorption between Au and N atom in DNA base 9 . It was observed that aptamer coated AuNPs were protected against salt aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Other dangerous pesticides have been detected using AuNP-based colorimetric aptasensors [24]. The sensing mechanism is summarized in Figure 11.…”
Section: Mechanism Of Positive Charge Generation Upon Reaction Of Dcnmentioning
confidence: 99%
“…61 Aptamers can be incorporated into a AuNP-based sensor as the molecular recognition element. Thiol modified aptamers can be covalently bound to AuNPs 62,63 through the thiol sulfur and gold surface, or unmodified aptamers can be adsorbed [64][65][66][67] onto the surface of the nanoparticle. Based on the covalent or non-specific interaction between aptamers and AuNPs, a number of different aptamer based AuNP sensors have been developed for a variety of targets, including small molecules.…”
Section: Aptamer-based Gold Nanoparticle Biosensorsmentioning
confidence: 99%
“…The interaction between aptamers and AuNPs is required to develop a sensing platform. [64][65][66][67] However, this interaction cannot be stronger than the interaction within the aptamer-target complex as the sensor relies upon the aptamer leaving the AuNP surface to preferentially bind its target molecule in solution. As the interaction between the aptamer and the AuNP is non-covalent, the relative strength of this interaction relative to the interaction within the aptamer-target complex determines the success of the sensor.…”
Section: Current Challenges With Aptamer-based Gold Nanoparticle Assaysmentioning
confidence: 99%
See 1 more Smart Citation